The Use of Powtoon as the Learning Media in Teaching English in Elementary School - Ardaningsih, Luh Ayu Novi; Adnyayanti, Ni Luh Putu Era (English Education Department STKIP Agama Hindu Singaraja, 2022)
The technology-based learning media is one of the essential media in the learning nowadays. Powtoon application is one of them that can apply by the teacher in conveying the material. Powtoon is an application where the creator can make the video look good, fun and attractive. On the other hand, it also more effective to operate. Powtoon can have a tremendous influence on the student's motivation in learning and help teachers in delivering the material in the classroom. Powtoon can be used on all levels of education, especially at the elementary school level, because Powtoon can attract students' attention and motivate them at the same time. This study aims to identify and share theoretical concepts and pedagogical practices of using Powtoon as the media for learning English at the elementary school level. This study used library research methods in obtaining the information which related to the utilization of Powtoon application on students and teacher’s self-development in elementary schools.